2019
DOI: 10.1080/20002297.2018.1565043
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium spp. target human CEACAM1 via the trimeric autotransporter adhesin CbpF

Abstract: Neisseria meningitidis, Haemophilus influenzae, and Moraxella catarrhalis are pathogenic bacteria adapted to reside on human respiratory mucosal epithelia. One common feature of these species is their ability to target members of the carcinoembryonic antigen-related cell adhesion molecule (CEACAM) family, especially CEACAM1, which is achieved via structurally distinct ligands expressed by each species. Beside respiratory epithelial cells, cells at the dentogingival junction express high levels of CEACAM1. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 67 publications
1
54
0
Order By: Relevance
“…However, the major consequence of this potential advantage is that any multivalent antagonistic molecule may effectively cross-link CEACAM1 receptors on opposing cells and thus potentially mimic a trans interaction or alternatively cross-link cis receptors with appropriate spatial organization that elicit undesired, functionally agonistic activation of CEACAM1-mediated inhibition. Microbes have developed clever strategies of activating CEACAM1 inhibitory function by exploiting the CEACAM1 IgV GFCC'C" surface through evolution of high affinity receptors [46] that outcompete CEACAM1 for binding and thus induce aggregation for purposes of attachment resulting in deliberate suppression of NK and T cell activity that allows for immune evasion by Neisseria, Fusobacterium and Helicobacter species [44,47,48,108] and suppression of anti-tumor immunity by Fusobacterium [49]. An unfortunate byproduct of this activity may be microbe-induced tumor initiation and/or promotion of tumor progression.…”
Section: Implications For Therapeutic Ceacam1 Blockadementioning
confidence: 99%
“…However, the major consequence of this potential advantage is that any multivalent antagonistic molecule may effectively cross-link CEACAM1 receptors on opposing cells and thus potentially mimic a trans interaction or alternatively cross-link cis receptors with appropriate spatial organization that elicit undesired, functionally agonistic activation of CEACAM1-mediated inhibition. Microbes have developed clever strategies of activating CEACAM1 inhibitory function by exploiting the CEACAM1 IgV GFCC'C" surface through evolution of high affinity receptors [46] that outcompete CEACAM1 for binding and thus induce aggregation for purposes of attachment resulting in deliberate suppression of NK and T cell activity that allows for immune evasion by Neisseria, Fusobacterium and Helicobacter species [44,47,48,108] and suppression of anti-tumor immunity by Fusobacterium [49]. An unfortunate byproduct of this activity may be microbe-induced tumor initiation and/or promotion of tumor progression.…”
Section: Implications For Therapeutic Ceacam1 Blockadementioning
confidence: 99%
“…This is of importance as there is little knowledge of the cellular adhesion mechanisms utilized by GBS, despite its role as a major neonatal pathogen. CEACAM engagement has also independently evolved in several Gram-negative human pathogens (Tchoupa et al, 2014(Tchoupa et al, , 2015Königer et al, 2016;Brewer et al, 2019;Conners et al, 2008;Virji et al, 1996;Hill et al, 2001;Bos et al, 1998). It is likely that -expressing GBS also adhere to human cells via CEACAMs, similarly to the Gram-negative bacteria (Bos et al, 1998;Gutbier et al, 2015;Tchoupa et al, 2014Tchoupa et al, , 2015Königer et al, 2016;Javaheri et al, 2016;Virji et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial ligands also bind to the A′GFCC′ face (Brewer et al, 2019;Conners et al, 2008;Villullas et al, 2007;Korotkova et al, 2008;Bonsor et al, 2018;Virji et al, 1999;Moonens et al, 2018). The H. pylori ligand HopQ uses a coupled folding and binding mechanism (Bonsor et al, 2018), and simulated docking indicated that the E. coli ligand AfaE binds to the CEACAM dimerization interface through the BE strands and DE loop of an incomplete Ig fold (Korotkova et al, 2008;Anderson et al, 2004).…”
Section: Identification Of Interacting Residues In the (-Igi3)-(ceacmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a growing list of pathogens has been found to express dedicated adhesins to specifically connect to human CEACAM family members, such as CEACAM1, CEA, and CEACAM6, which are exposed on the apical surface of human epithelial cells. CEACAM-binding microorganisms comprise Neisseria gonorrhoeae (causative agent of the venereal disease gonorrhea), Neisseria meningitidis (bacterial meningitis), Haemophilus influenzae (pneumonia, bacterial meningitis), Haemophilus aegyptius (purulent conjunctivitis), Helicobacter pylori (chronic gastritis, stomach cancer), Moraxella catarrhalis (otitis media, sinusitis), Fusobacterium nucleatum (periodontal disease), pathogenic Escherichia coli strains (Adherent-invasive E. coli, Diffusely adherent E. coli; involved in Crohn's disease), and the yeast Candida albicans (candidiasis, systemic infections) (26)(27)(28)(29)(30)(31)(32)(33)(34)(35). It is important to mention that almost each of these pathogens employs a structurally distinct adhesive protein to bind human CEACAMs, implying that these adhesins have evolved independently multiple times in a striking form of convergent evolution (7,15,32,(36)(37)(38)(39).…”
Section: Ceacam Family Members and Their Role As Microbial Targetsmentioning
confidence: 99%